(untitled) (Journal of the Bangladesh Agricultural University, 2013)
Landmark-based morphometric and meristic analysis of pond, haor and estuary populations of Glossogobius giuris (Hamilton,1822) (Perciformes:Gobiidae) were done to find out variations among the three stocks. Samples were collected from three different regions such as pond of Mymensingh, haor of Kishoreganj and estuary of Barisal. Significant differences (*P<0.01) were observed in 13 general morphometric and 23 size adjusted landmark-based morphometric measurements among three stocks. Among the 11 meristic counts the first dorsal fin rays (D1FR), transverse scale above lateral line (TSALL), branchiostegal rays and number of vertebrae were same among fishes of these stocks. In case of pectoral fin rays (PcFR) and transverse scale on lateral line (TSOLL) the haor stock was significantly different from other two stocks. In discriminant space, pond stock was isolated from other two stocks. On the other hand, haor and estuary stocks showed very close relationship. A dendrogram based on the hierarchical cluster analysis using size adjusted general morphometric and landmark measurements formed two main clusterspond stock in one cluster and other two stocks (haor and estuary) remained in another cluster. It indicates that pond stock was separated. The second cluster explained that haor and estuary stocks had very close relationship. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14931 J. Bangladesh Agril. Univ. 10(2): 375-384, 2012